Pengaruh Mekanisme Corporate Governance, Ukuran Perusahaan, Leverage, Dan Pertumbuhan Investasi Terhadap Kualitas Laba(Studi Empiris pada Perusahaan Manufaktur yang terdaftardi Bursa Efek Indonesia periode 2010-2013) - Riyani, Putri; , Dr. Triyono, S.E., M.Si (2015)
The purpose of this research is to examine the influence of the factors that affect the earnings quality, corporate governance mechanisms, which include: the proportion of independent board, institutional ownership, managerial ownership and audit committee, size, leverage and investment growth. The research used samples from 227 manufacturing companies listed on Indonesia Stock Exchange, by using purposive sampling method which were published financial report among 2010-2013. The analysis method of this research used multi regression. The results of this research show that proportion of independent board was significantly negative effect on the earnings quality. There is a positive effect of managerial ownership, leverage and Investment Growth on the warning quality. There is a negative effect Institutional Ownership, Audit Committee, and Size on the earning quality.